Organ donation: from diagnosis to transplant. Issue 2 (April 2020) - Robba, Chiara; Fossi, Francesca; Citerio, Giuseppe
Abstract : Purpose of review: Organ transplantation has largely expanded over the last decades and despite several improvements have been made in the complex process occurring between the identification of organ donors and organ transplant, there is still a chronic inability to meet the needs of patients. Consequently, the optimization of the transplant process through its different steps is crucial, and the role of the intensivists is fundamental as it requires clinical, managerial and communication skills to avoid the loss of potential donors. The purpose of this review is to provide an update on the transplant process from the early identification of the donor, to transplant. The two main pathways of organ donation will be discussed: donation after death by neurologic criteria and the donation after cardiac death (DCD). Recent findings: Recent evidence demonstrates that appropriate intensive care management is fundamental to increase organ availability for transplantation. The expansion of pool donation requires a strong legal framework supporting ethical and organizational considerations in each country, together with the implementation of physicians' technical expertise and communication skills for family involvement and satisfaction. New evidence is available regarding organ donor's management and pathway. The importance of checklists is gaining particular interest according to recent literature. Recent clinical trials including the use of naloxone, simvastatin and goal directed hemodynamic therapies were not able to demonstrate a clear benefit in improving quality and number of transplanted organs. Ethical concerns about DCD are recently being raised, and these will be discussed focusing on the differences of outcome between controlled and uncontrolled procedure. Summary: The major change in the process of organ donation has been to implement parallel DCD and donation after brain death pathways. However, more research is needed for improving quality and number of transplanted organs.